Variation in exposure in neighborhoods of Dhaka, Bangladesh across different environmental pathways: The influence of human behavior on fecal exposure in urban environments - Nuhu Amin; Suraja Raj; Jamie Green; Shahjahan Ali; Sabrina Haque; Yuke Wang; Wolfgang Mairinger; Tanvir Ahmed; George Joseph; Mahbubur Rahman; Christine L. Moe (PLoS ONE, 2026)
Background Poor sanitation and fecal sludge management contribute to fecal contamination in Dhaka’s urban environment. An exposure assessment through ten environmental pathways was conducted using the SaniPath TM tool to understand the exposure to fecal contamination. Methods Data collection took place from 25/04/2017 to 30/01/2018 in ten neighborhoods: four low-income, four high-income, and two transient/floating neighborhoods. A total of 1000 environmental samples were analyzed using the IDEXX QuantiTray/2000 method with IDEXX-Colilert-24 ® media for the most probable number (MPN) of E. coli . Additionally, 823 household surveys, 28 community surveys, and 35 school surveys on exposure-related behaviors were conducted. Bayesian methods were used to estimate monthly E. coli exposure levels and population exposure percentages for each environmental pathway in the neighborhoods. Results Findings revealed that children (aged 5–12 years) in low-income and floating neighborhoods had more frequent contact with most environmental pathways (at least one contact per week or month), except surface water, compared to children in high-income neighborhoods. Dominant exposure pathways varied by neighborhood and socioeconomic status. Children experienced higher estimated monthly fecal exposure doses than adults, primarily through ingestion of contaminated municipal water (all community average = 59.2% of population exposed, either adults or children) and contact with open drains (52.3%) and surface waters (29.0%). Adults were mainly exposed via contaminated municipal water (54.2%), produce (87.0%), and street food (64.5%), which were frequently consumed. Conclusions These results highlight substantial risks of fecal exposure across diverse urban settings in Dhaka. Integrated, multisectoral, and sustainable approaches are critical to reduce exposure and protect public health. Behavior change interventions targeting children and caregivers can further mitigate these risks and help ensure long-term public health improvements.